Jianpi Yangzheng Xiaozheng granule induced ferroptosis to suppress gastric cancer progression through reprogramming lipid metabolism via SCD1/Wnt/β-catenin axis - Wang, Xiangyang; Li, Jingxiao; Qin, Rong; Yin, Yi; Li, Jiepin; Lin, Sitian; Zou, Xi (Frontiers in Molecular Biosciences, 2025)
The incidence of Poorly cohesive carcinoma (PCC) has steadily risen in recent years, posing a significant clinical challenge. To reveal the anti-tumor effects of Jianpi Yangzheng Xiaozheng granule (JPYZXZ) in PCC, an initial investigation was performed using CCK-8, colony formation, scratch, and transwell assays. This was followed by network pharmacology studies to gain a deeper understanding of JPYZXZ’s impact on gastric cancer (GC). Then reactive oxygen species (ROS), Fe2+, malondialdehyde (MDA), glutathione (GSH), Oil Red O staining, BODIPY493/503, triglyceride (TG), and cholesterol (TC) assay kits and western blot (Wb) analysis were applied to exam the regulatory effects of JPYZXZ on ferroptosis and lipid metabolism. Additionally, molecular docking studies and Wb analysis were used to further investigate the mechanisms of JPYZXZ on PCC. Finally, in vivo animal studies were conducted. The results show that JPYZXZ can inhibit the proliferation and migration of PCC cell. It increases the levels of ROS, Fe2+, MDA, while declining the content of GSH, TC, TG, and lipid droplet accumulation within cellular compartments. Wb indicates that JPYZXZ can negatively regulate the expression of proteins, including glutathione peroxidase 4 (GPX4), cystine/glutamate antipoter SLC7A11 (xCT), fatty acid synthase (FASN), and acetyl coenzyme A carboxylase 1 (ACC1). Furthermore, ferrostatin-1 (fer-1) is able to reverse the effects of JPYZXZ on the aforementioned markers of ferroptosis and lipid metabolism. Molecular docking analyses reveal that JPYZXZ exhibits a favorable binding affinity towards Stearoyl-Coenzyme A desaturase 1 (SCD1). Mechanism studies demonstrate that JPYZXZ is capable of down-regulating the expressions of proteins like SCD1, β-catenin, GPX4, and xCT, which is analogous to the effects of SCD1 knockdown and the application of SCD1 inhibitor A939572. Nevertheless, when SCD1 is knocked down, JPYZXZ is unable to further downregulate the expressions of these proteins. Animal studies have corroborated the in vitro tumor-inhibiting effects of JPYZXZ. Therefore, this study offers the first evidence that JPYZXZ inhibits PCC progression by orchestrating ferroptosis and altering lipid metabolism, mediated by the SCD1/Wnt/β-catenin pathway.